Estudo teórico de espectroscopia das moléculas diatômicas, AlC e GaC, e estudo de propriedades físico-químicas de microclusters de AlnC, AlnSi e GanC,(n=1-7) - Fernandes, Gabriel Freire Sanzovo [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This work involves using methods of molecular quantum chemistry to characterize small molecule agglomerates formed by aluminum atoms and gallium-doped with a carbon atom or a silicon atom, AlnC, and GanC and AlnSi (n = 1-7), in which the purpose is to verify whether the Hume-Rothery rules could be valid for these systems. For the simplest system, AlC and GaC, the methods of multiconfiguration self-consistent field were used in a complete active space (CASSCF) and multireference configuration interaction (MRCI) to characterize both the ground state, as several excited states, including those still previously uncharacterized in the literature. These methods include both static correlation and dynamic correlation and are the most suitable methods for the characterization of excited states and thus for the determination of the electronic spectra and radiative transition probabilities of these states. The AlnC agglomerates, and GanC and AlnSi (n = 1-7) were characterized using a Hm-GGA approximation of the density functional theory (M06) with the basis set of functions 6-311 ++ G (3df, 3pd), in which the search for the global minimum energy conformations was performed by geometry optimizations from various initial geometries, taking into account possible different spatial symmetries, as well as different spin multiplicities. It was found that the lowest energy conformers have high symmetry in the case of smaller agglomerates (AlnC, GanC and AlnSi (n <5)), whereas the larger agglomerates have low spatial symmetry due to a rearrangement of aluminum atoms, or gallium around the carbon atom, which has all unsaturated bonds. Regarding the excited states of the agglomerates, it was found that doped systems have oscillations due the parity of the number of matrix atoms, with much larger excitation energy in the pure agglomerates of aluminum and gallium, particularly for systems with few atoms... (Completo abstract click electronic access below)

Este trabalho consiste em utilizar métodos da química quântica molecular para caracterizar pequenos aglomerados moleculares formados por átomos de alumínio e gálio e dopados com um átomo de carbono e um átomo de silício, AlnC, GanC e AlnSi (n=1-7), com a finalidade de verificar se as regras de Hume-Rothery poderiam ser válidas para estes sistemas. Para o sistema mais simples, AlC e GaC, foram utilizados os métodos do campo auto-consistente multiconfiguracional num espaço ativo completo (CASSCF) e interação de configurações multireferencial (MRCI) para caracterizar tanto o estado fundamental, como vários estados excitados, incluindo àqueles ainda não caracterizados anteriormente na literatura. Estes métodos incluem tanto a correlação estática quando a correlação dinâmica e são os mais adequados para a caracterização de estados excitados e consequentemente para a determinação dos espectros eletrônicos e das probabilidades de transição radiativa destes estados. Os aglomerados AlnC, GanC e AlnSi (n=1-7) foram caracterizados a teoria do funcional densidade (M06) com o conjunto de funções de base 6-311++G(3df,3pd), onde se buscou as conformações de mínimo de energia global, realizando otimizações de geometria a partir de diversas geometrias iniciais, levando em consideração as possíveis simetrias espaciais distintas, assim como diferentes multiplicidades de spin. Verificou-se que os confôrmeros de mais baixa energia apresentam alta simetria no caso dos aglomerados menores, (AlnC, GanC e AlnSi (n < 5)), enquanto que os aglomerados maiores apresentam baixa simetria espacial, devido a uma reorganização dos átomos de alumínio ou do gálio ao redor do átomo de carbono, o qual possui todas as ligações saturadas. Em relação aos estados excitados dos aglomerados, verificou-se que os sistemas dopados... ( Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Espectroscopia molecular; Moleculas; Semicondutores dopados; Quimica quantica; Doped semiconductors